2008
DOI: 10.1111/j.1939-3938.2008.00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Injuries to the cervix in sexual trauma

Abstract: Research on genital injury in sexual assault is limited and few articles have documented injuries to the cervix in sexual assault victims. This review focuses on reviewing and critically evaluating available literature on injuries of the cervix associated with rape, sexual trauma, and some other circumstances. Based on this evaluation, topics for future research are suggested. Nursing and medical studies were examined for this review. The collective studies date from 1991 to 2004. Although multiple articles we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The scope has been as narrow as injury to a specific part of genital tissue (Keller & Nelson, 2008) to the outcomes achieved by sexual assault nurse examiners (SANE) or forensic nurse examiners (FNE) in contrast to post-sexual assault care offered by physicians (Campbell et al, 2006). As the majority of reported assaults for which data exists were perpetrated by a male assailant upon a female victim, the mechanism of injury in sexual assault is most commonly blunt force trauma inflicted by a penis.…”
Section: Description Of the Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…The scope has been as narrow as injury to a specific part of genital tissue (Keller & Nelson, 2008) to the outcomes achieved by sexual assault nurse examiners (SANE) or forensic nurse examiners (FNE) in contrast to post-sexual assault care offered by physicians (Campbell et al, 2006). As the majority of reported assaults for which data exists were perpetrated by a male assailant upon a female victim, the mechanism of injury in sexual assault is most commonly blunt force trauma inflicted by a penis.…”
Section: Description Of the Injurymentioning
confidence: 99%
“…There are many factors which may affect risk of HIV transmission for example the age of the patient and attendant postmenopausal changes in vaginal lubrication (Poulos & Sheridan, 2008). A recent review examined the evidence available specific to cervical injury and found most commonly that there was erythema only to the cervix following sexual assault (Keller & Nelson, 2008). Unfortunately, the literature available is dated and suffers from lack of consistency in documentation and examination of injuries as well as what caused the specific injuries.…”
Section: Description Of the Injurymentioning
confidence: 99%
“…Rough sex can alter the integrity of the epithelial barrier by causing TEARS, 8 and cervical swelling is noted with forced sex. 11 Even without visible TEARS, genitoanal injuries may facilitate HIV transmission by penetrating the epithelial barrier, drawing HIV target cells into the genital tract, and/or creating a proinflammatory response in the mucosal microenvironment—similar to sexually transmitted infections (STIs). 12 Hormone levels and menstruation also have confounding effects through influences on vaginal epithelial and mucosal integrity.…”
Section: Introductionmentioning
confidence: 99%